2017
DOI: 10.15760/comminfolit.2017.11.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Library Experience and Information Literacy Learning of First Year International Students: An Australian Case Study

Abstract: This qualitative case study provides fresh understandings about first year undergraduate international students' library and information use at an Australian university, and their associated information literacy learning needs. The findings provide evidence to inform the development of library spaces and information literacy responses that enhance international students' transition and learning. The study was conducted in 2015 as part of a project that simultaneously investigated the same topic at three US uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
0
18
0
3
Order By: Relevance
“…A picture of students using Google or Google Scholars for finding information is not new. [14] reported that the majority of students they studied were utilizing Google for finding information. More to that, [6] even find more compelling result for their study, it was not only undergraduate students who use Google, but even postgraduate students and lecturers were also use Google when it comes for getting information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A picture of students using Google or Google Scholars for finding information is not new. [14] reported that the majority of students they studied were utilizing Google for finding information. More to that, [6] even find more compelling result for their study, it was not only undergraduate students who use Google, but even postgraduate students and lecturers were also use Google when it comes for getting information.…”
Section: Resultsmentioning
confidence: 99%
“…However, in both studies conducted by [14] and [6] reported that Google were only the initial step the students use for information search. It also being used only for getting ideas about the right keywords or terms for their search.…”
Section: Resultsmentioning
confidence: 99%
“…The following are the stages in listening ; (1) Stage of listening, at this stage we just hear everything that is said by the speaker in the speech or conversation. So we are still in the hearing stage [26], [27]. (2) The stage of understanding, after we hear, there is a desire for us to understand or understand the contents of the conversation which are delivered by the speaker [11], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Another study on the needs of the international students in Australia, it was found and pointed out that the development of library space and information literacy programs significantly boosted and enhanced students' transition and learning [21]. Furthermore, the librarians' role in the implementation of information literacy and maker education is underlined [22].…”
Section: Information Literacy Skills Factormentioning
confidence: 99%
“…Physical space, virtual space [13,17,18,22] Information Literacy Skills (Moderating) Cognitive, ethical [2,8,15,16,19,20,21] Utilization of WBIS (DV) Output, outcome [4,7,8,9,10]…”
Section: Library Learning Environment (Iv)mentioning
confidence: 99%